Distribution and Analysis of Responses to Extreme Weather Phenomena through Twitter - Kedhaton, Arum Sekar; Arif, Nursida (TDMRC, Universitas Syiah Kuala, 2023)
The aim of this research is to map the distribution of extreme weather events occurring in Indonesia through Tweets, which are subsequently validated with actual conditions, and to analyze the public sentiment regarding extreme weather. The research utilizes the Social Network Analysis (SNA) method, obtained from the netlytic.org website. Data collection was conducted for five days, from March 23 to March 27, 2023. However, only 249 tweets, or approximately 31% of the total, were related to extreme weather, specifically stormy rain phenomena in their true sense. The stormy rain phenomena were identified to have occurred on March 23 and March 27, 2023. There was also a hailstorm phenomenon in Pekanbaru, Riau. The highest occurrence of extreme weather events was recorded in several regions of Indonesia, including Bandung, Surabaya, Malang, Jakarta, and Riau. Most Twitter users' responses were negative (49%), followed by neutral responses (45%), and positive responses (6%).